European Regulatory Aspects of the Organizational Law of Public Administration - Sabjanics, István; Gerencsér, Balázs Szabolcs (General Principles and Challenges of Public Administration Organization in Central Europe, 2024)
the state. This paper goes beyond the traditional approach to public administration to reveal the interrelationships that today limit the organizational autonomy of individual states. Following an examination of the basic theoretical issues of organizational law, the paper addresses the relationship between administrative organization and sovereignty. In doing so, it examines international law and European Union (EU) norms containing rules directly or indirectly affecting administrative organization. The study particularly highlights the function of international organizations in making best practices available to states. EU primary and secondary legislation appears to respect EU Member States’ autonomy, but there are also various rules that oblige EU Member States to shape their administrative organization. There is also a focus on EU agencies, European Groupings of Territorial Cooperation, and other bodies linked to national administrations as specialised EU administrative structures. Overall, the study contributes to an examination of the extent to which EU Member States’ autonomy is limited today and by what means. KEYWORDS public administration, organization, structure, sovereignty, autonomy, agency, Council of Europe, European Union, secondary legislation, soft law Bibliography Abbott, K. W., Snidal, D. (2000) ‘Hard and Soft Law in International Governance’, International Organization, 54(3), pp. 421–456 [Online]. Available at: https://doi.org/10.1162/002081800551280 (Accessed: 11 February 2024). Ádány, T. (2020) ‘A szuverenitás gyakorlásának nemzetközi jogi keretei’ in Csink, L., Schanda, B., Varga, Zs. A. (eds.) A Magyar közjog alapintézményei. 1st edn. Budapest: Pázmány Press, pp. 229–256. Bastos, F. B. (2021) ‘Doctrinal Methodology in EU Administrative Law: Confronting the “Touch of Stateness”’, German Law Journal, 22, pp. 593–624 [Online]. Available at: https://doi.org/10.1017/glj.2021.20 (Accessed: 11 February 2024). Baumgart, L., Muster, J. (2023) ‘Organization not found: Ein organisationssoziologischer Blick auf die Digitalisierung als Verwaltungsreform’, Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO), 54, pp. 177–185 [Online]. Available at: https://doi.org/10.1007/s11612-023-00681-w (Accessed: 11 February 2024). Bobek, M. (2017) ‘The effects of EU law in the national legal systems’ in Barnard, C., Peers, S. (eds.) European Union Law. 2nd edn. Oxford: Oxford University Press, pp. 143–176. Craig, P. (2011) ‘Shared Administration and Networks: Global and EU Perspectives’ in Anthony, G., Auby, J.-B., Morison, J., Zwart, T. (eds.) Values in Global Administrative Law. 1st edn. Oxford and Portland: Hart Publishing, pp. 81–116. Craig, P. (2012) EU Administrative Law. 2nd edn. Oxford: Oxford University Press. Available at: https://doi.org/10.1093/acprof:oso/9780199568628.001.0001. Crawford, J. (2012) Brownlie’s Principles of Public International Law. 8th edn. Oxford: Oxford University Press. Edwards, D. (1996) ‘Judicial Activism—Myth or Reality? Van Gend en Loos, Costa v. ENEL and the Van Duyn Family Revisited’ in Campbell, A. I. K., Voyatzi, M. (eds.) Essays in the Honour of Lord Mackenzie-Stuart. Gosport: Trenton, pp. 29–67. Fox, W. F. (2012) Understanding Administrative Law. 6th edn. Durham: Carolina Academic Press – LexisNexis. Hoffmann, I. (2015) Gondolatok a 21. századi önkormányzati jog fontosabb intézményeiről és modelljeiről – A nyugati demokráciák és Magyarország szabályozásainak, valamint azok változásainak tükrében. Budapest: ELTE Eötvös Publishers. Jakab, R. (2020) ‘The Influence of EU Law on Public Administration in New Member States’, Public Governance, Administration and Finances Law Review, 5(1), pp. 48–61 [Online]. Available at: https://doi.org/10.53116/pgaflr.2020.1.3 (Accessed: 12 February 2024). Jennings, R., Watts, A. (eds.) (2008) Oppenheim’s International Law. 9th edn. Oxford: Oxford University Press. Available at: https://doi.org/10.1093/law/9780582302457.001.0001. Kálmán, J. (2013) ‘Az európai ügynökségek és a Meroni-doktrína’, De iuris prudentia et iuris publico: Jog- és politikatudományi folyóirat, 8(3), pp. 57–73 [Online]. Available at: https://real.mtak.hu/13841/ (Accessed: 12 February 2024). Kardos, G. (2018) ‘Az államok szuverén egyenlősége’, Internetes Jogtudományi Enciklopédia [Online]. Available at: http://ijoten.hu/szocikk/az-allamok-szuverenegyenlosege (Accessed: 31 July 2023). Koopmans, T. (2011) ‘Globalisation of Administrative Law – the European Experience’ in Anthony, G., Auby, J.-B., Morison, J., Zwart, T. (eds.) Values in Global Administrative Law. 1st edn. Oxford and Portland: Hart Publishing, pp. 393–406. Láncos, P. L. (2022) The Many Facets of EU Soft Law. Budapest: Pázmány Press. OECD (2023) Government at a Glance 2023. Paris: OECD Publishing [Online]. Available at: https://doi.org/10.1787/3d5c5d31-en (Accessed: 12 February 2024). Polt, P. (2019) A költségvetés büntetőjogi védelmének egyes elméleti és gyakorlati kérdései – Hazai gyakorlat és uniós mechanizmusok. Budapest: Dialóg Campus. Rasmussen, M. (2014) ‘Revolutionizing European Law: The History of the Van Gend en Loos Judgment’, European Journal of International Law, 25(1), pp. 136–163 [Online]. Available at: https://doi.org/10.1093/ejil/chu023 (Accessed: 12 February 2024). Rose-Ackerman, S., Perroud, T. (2013) ‘Policymaking and Public Law in France: Public Participation, Agency Independence, and Impact Assessment’, Columbia Journal of European Law, 19(2), pp. 225–312 [Online]. Available at: https://hal.science/hal-01699022 (Accessed: 31 July 2023). Sand, P. H., McGee, J. (2022) ‘Lessons Learnt from Two Decades of International Environmental Agreements: Law’, International Environmental Agreements: Politics, Law and Economics, 22, pp. 263–278 [Online]. Available at: https://doi.org/10.1007/s10784-022-09572-9 (Accessed: 12 February 2024). Saurer, J. (2010) ‘Supranational Governance and Networked Accountability Structures: Member State Oversight of EU Agencies’ in Rose-Ackerman, S., Lindseth, P. L. (eds.) Comparative Administrative Law. Cheltenham: Edward Elgar, pp. 618–631. Available at: https://doi.org/10.4337/9781849808101.00050. Snyder, F. (1993) ‘The Effectiveness of European Community Law: Institutions, Processes, Tools and Techniques’, The Modern Law Review, 56(1), pp. 19–54 [Online]. Available at: https://doi.org/10.1111/j.1468-2230.1993.tb02852.x (Accessed: 12 February 2024). Stene, E. O. (1940) ‘An Approach to a Science of Administration’, The American Political Science Review, 34(6), pp. 1124–1137 [Online]. Available at: https://doi.org/10.2307/1948193 (Accessed: 12 February 2024). Tamás, A. (2010) A közigazgatási jog elmélete. Budapest: Szent István Társulat. Terpan, F. (2014) ‘Soft Law in the European Union – The Changing Nature of EU Law’, European Law Journal, 21(1), pp. 68–96 [Online]. Available at: https://doi.org/10.1111/eulj.12090 (Accessed: 12 February 2024). Varga, A. (2021) A helyi önkormányzáshoz való jog alapvető kérdései. Budapest: Pázmány Press. Varga, Zs. A. (2020) ‘Magyarország szuverenitása’ in Csink, L., Schanda, B., Varga, Zs. A. (eds.) A Magyar közjog alapintézményei. 1st edn. Budapest: Pázmány Press, pp. 257–287. Waldo, D. (1948) The Administrative State. New York: Ronald Press. Waldo, D. (1955) The Study of Public Administration. Garden City, NY: Doubleday & Co. Joseph, H.H., Weiler, J.H.H. (2003) ‘Rewriting Van Gend en Loos: Towards a Normative Theory of ECJ Hermeneutics’ in Wiklund, O. (ed.) Judicial Discretion in European Perspective. 1st edn. The Netherlands: Kluwer Law International. International documents Report on the Rule of Law, adopted by the Venice Commission at its 86th Plenary Session (Venice, 25–26 March 2011), CDL-AD(2011)003rev. Recommendation CM/Rec(2007)7 of the Committee of Ministers to member states on good administration. CDL-PI(2023)016 Ukraine – Information on the follow-up to the urgent joint opinion on draft law No. 5068. CDL-AD(2023)015 France – Joint opinion on the Superior Council of Magistracy, adopted at the 135th Plenary Session (Venice, 9–10 June 2023). CDL-AD(2022)045 Romania – Urgent opinion on three laws concerning the justice system, adopted at the 133rd Plenary Session (Venice, 16–17 December 2022). CDL-AD(2021)036 Hungary – Opinion on amendments to the Acts on courts and judges, adopted at the 128th Plenary Session (15–16 October 2021). CDL-AD(2012)011 Opinion on the Act on the Rights of Nationalities of Hungary. CDL-AD(2015)015 Opinion on Media Legislation of Hungary. CDL-AD(2010)040 Report on European Standards regarding the Independence of the Judicial System: Part II – The Prosecution Service. Opinion No. 7 (2012) of the Consultative Council of European Prosecutors on the Management of the Means of Prosecution Services. Council Regulation (EEC) No 337/75 establishing a European Centre for the Development of Vocational Training. Council Regulation (EEC) No 1365/75 on the creation of a European Foundation for the Improvement of Living and Working Conditions. The Operating Framework for the European Regulatory Agencies, COM(2002) 718 final, 5.